Osmolarity Changes after Mannitol Administration in Cerebral Edema Patients - Tampubolon, Monica; Iqbal, Kiki M.; Pujiastuti, R. A. Dwi (Journal of Society Medicine, 2023)
Introduction: Cerebral edema is commonly associated with cerebral pathology, and the clinical manifestation is greatly influenced by the underlying damaged tissue. Mannitol is the most widely used osmotic agent to reduce intracranial pressure. Giving osmotic therapy with 20% mannitol has the benefit of reducing ICP but can increase plasma osmolarity which can increase the risk of kidney disorders in patients with cerebral edema. This study aimed to assess osmolarity changes after mannitol administration in cerebral edema patients. Method: This is a pre-experimental study with a one-group pretest-posttest design. The research subjects were taken from the patient population of H. Adam Malik General Hospital Medan and Network Hospitals. The determination of research subjects was carried out according to the non-random sampling method consecutively and obtained as many as 32 research samples conducted from December 2022-April 2023. To determine changes in plasma osmolarity, a paired t-test was performed. Results: The mean osmolarity before mannitol administration was 303.74±11.59 mOsm/L and after mannitol administration was 307.01±14.83 mOsm/L, with an average change in osmolarity was 3.27±12.19 mOsm/L. There were no significant changes in mean plasma osmolarity after administration of mannitol (p=0.139). Based on the analysis of laboratory components, a significant increase in BUN values was found after the administration of mannitol (p=0.003). Conclusion: In patients with cerebral edema, mannitol treatment is generally safe and does not result in clinically significant electrolyte abnormalities. But during and after mannitol therapy, electrolyte and renal function monitoring is required.